A Note on “Multinational Corporate Pricing Policy in the Developing Countries” - Jagpal, Harsharanjeet Singh (Journal of International Business Studies, 1977)
Professor Leff proposed in a recent article1 that multinational corporations and their host countries would gain mutually if the former reduced their prices. The rationale for this thesis deserves careful examination since the economic implications are far reaching.